2012
DOI: 10.1177/1098300712449868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Matching Instruction Difficulty to Reading Level for Students With Escape-Maintained Problem Behavior

Abstract: The effects of a literacy intervention matching student skill level with academic performance demands were examined through a multiple baseline across participants design. The dual dependent variables were problem behavior and academic engagement. Four students in Grades 2 or 3 who exhibited low academic performance and problem behavior during reading instruction participated. Functional behavioral assessment and oral reading fluency assessment indicated that each of the students (a) was at risk for reading di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…Skill building activities as part of the function‐based intervention typically included development of academic skills though they were infrequently included ( n = 5). One study with three participants (Sanford & Horner, ) placed all three students in a new reading program (Reading Mastery; Science Research Associates, ) as part of the function‐based intervention. Vocabulary instruction ( n = 1) and development of decoding skills ( n = 1) were also present.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Skill building activities as part of the function‐based intervention typically included development of academic skills though they were infrequently included ( n = 5). One study with three participants (Sanford & Horner, ) placed all three students in a new reading program (Reading Mastery; Science Research Associates, ) as part of the function‐based intervention. Vocabulary instruction ( n = 1) and development of decoding skills ( n = 1) were also present.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies reported at least some information regarding intervention fidelity. (Christensen, Young, & Marchant, ; Fairbanks, Sugai, Guardino, & Lathrop, ; Filter & Horner, ; Haydon, ; Lane et al., ; March & Horner, ; McComas, Goddard, & Hoch, ; Payne et al., ; Preciado, Horner, & Baker, ; Sanford & Horner, ; Trussell, Lewis, & Stichter, ). One study reported collecting fidelity data for participant training and use of the peer component of the intervention, all of which were at acceptable levels (Christenson et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefits in understanding the involvement of behaviour problems among youth and informing the design of interventions to reduce behaviour problems [3]. Educators must be able to understand the behaviour and academic problems of students so that they can help the problems they face and prevent difficulties in the future [4].…”
Section: Introductionmentioning
confidence: 99%
“…Research also suggests that teachers must be proficient in classroom management to improve the reading skills of students with EBD (J. Garwood, Vernon‐Feagans, & Family Life Project Key Investigators, ). For example, students with EBD may display problem behaviors to avoid or in response to reading tasks (Sanford & Horner, ), which may result in the loss of substantial instructional time (J. McKenna & Ciullo, ). However, researchers have also theorized that the relationship (e.g., causal, moderating, or mediating) between problem behaviors and academic achievement is distinct across students (Gresham, ).…”
Section: Introductionmentioning
confidence: 99%